Growth and yield performance of five purple sweet potato (Ipomoea batatas) accessions on colluvium soil - Mohammad Yusoff, Martini; Abdullah, Siti Nurjiah; Abd Halim, Mohd Ridzwan; Shari, Erwan Shah; Ismail, Nur Arina; Mohammad Yusoff, Masnira (Universiti Putra Malaysia Press, 2018)
A study was conducted to evaluate the growth and yield performance of five purple sweet potato accessions on colluvium soil at Field 2, Universiti Putra Malaysia, Serdang, Selangor. The treatments comprised five purple sweet potato accessions (Accessions 1, 2, 3, 5, and 6) arranged in completely randomized design with four replications. Maximum tuber yield of purple sweet potato was highest (p < 0.05) in Accession 6 (34,563 kg ha-1) compared to the lowest yield in Accession 3 (9,331 kg ha-1). This was followed by Accession 2 (22,031 kg ha-1), Accession 1 (21,094 kg ha-1), and Accession 5 (22,900 kg ha-1). A similar trend was observed for crop growth rate (CGR) with the highest (199 kg ha-1 day-1 ) in Accession 6 and the lowest (60 kg ha-1 day-1 ) in Accession 3 (p < 0.05). Accession 6 reached the critical leaf area index (LAIcrit) of 2.79 at 90% of intercepted radiation compared to the Accessions 1, 2, 3, and 5 that did not reach the LAIcrit. Unexpectedly, the highest total intercepted photosynthetically active radiation (PAR) was recorded by Accession 3 (340 MJ m-2), whereas Accession 6 showed the lowest (309 MJ m-2). In contrast, the highest radiation use efficiency (RUE) was obtained by Accession 6 with 7.58 g MJ-1 and the lowest was Accession 3 (2.16 g MJ-1 ). However, there was no significant difference in RUE among the rest of the accessions, except for Accession 6. To maximize the tuber yield, Accession 6 is the choice for cultivation in colluvium soil.